Computer science principles : the foundational concepts of computer science - Hare, Kevin (Georgia : Yellow Dart Publishing, 2018)
Computer science is the world's fastest growing field of study, and this growth is showing no signs of slowing down. As a new field, computer science can seem intimidating, but it should not be scary to learn or difficult to understand. If you have ever turned on a phone or surfed the Internet then you have used a computer and should have a basic understanding of what happens when you click the mouse or touch the screen$1 (Band how fast it happens! Computer Science Principles introduces the creative side of computing. Once you've made your way through this book, you'll be editing photos, designing websites, coding JavaScript, and getting organized with spreadsheets$1 (Band along the way you'll learn the foundational concepts of computer science. How do computers convert information into ones and zeros and send it thousands of miles in a blink of the eye? What is an IP address? What do TCP/IP, DNS, HTML, and CSS stand for? How can a hard drive store large movies and thousands of songs? How can secrets be sent in plain sight? These questions$1 (Band more$1 (Bare answered in Computer Science Principles.s
Keywords: COMPUTER PROGRAMMING